2013
DOI: 10.3390/toxins5101767
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Two Lectins from Dwarf Elder (Sambucus ebulus L.) Blossoms Related to the Sam n1 Allergen

Abstract: Sambucus species contain a number of lectins with and without antiribosomal activity. Here, we show that dwarf elder (Sambucus ebulus L.) blossoms express two d-galactose-binding lectins that were isolated and purified by affinity chromatography and gel filtration. These proteins, which we named ebulin blo (A-B toxin) and SELblo (B-B lectin)—blo from blossoms—were subjected to molecular characterization and analysis by MALDI-TOF mass spectrometry and tryptic peptide fingerprinting. Both lectins share a high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…We have previously reported that oral ingestion of ebulin f at 5 mg/kg of body weight killed 50% of the animals in 10 days, while those that survived recovered after 30 days from the administration of the toxin [ 10 ]. We obtained similar results following nasal administration of ebulin blo at the same dose [ 18 ]. We estimated, therefore, an approximate LD 50 of 5 mg/kg of body weight for both oral and nasal administration, in contrast to the LD 50 value of 2.8 mg/kg body weight for i.p.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…We have previously reported that oral ingestion of ebulin f at 5 mg/kg of body weight killed 50% of the animals in 10 days, while those that survived recovered after 30 days from the administration of the toxin [ 10 ]. We obtained similar results following nasal administration of ebulin blo at the same dose [ 18 ]. We estimated, therefore, an approximate LD 50 of 5 mg/kg of body weight for both oral and nasal administration, in contrast to the LD 50 value of 2.8 mg/kg body weight for i.p.…”
Section: Introductionmentioning
confidence: 59%
“…Previous studies have described the toxicity of ebulin f and ebulin blo in six-week-old mice [ 11 , 18 ]. Early intestinal targets were the transit amplifying cells present in the small intestine crypts, as well as the cells of the large intestine crypts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, as will be indicated below, ebulin f displays a significant oral toxicity in mice, it is important to reduce the influence of ebulin f without affecting its antioxidant capacity. A short heating of ripe fruit extracts only reduced the content of total phenols and the antioxidant and free-scavenging activities by up to 13.5% but completely sensitized ebulin f to pepsin [ 36 ].…”
Section: Isoforms Of Ebulinmentioning
confidence: 99%
“…Dwarf elder blossoms also contain an isoform of ebulin, which we named ebulin blo, together with a homodimeric lectin we called SELblo [ 36 ]. MALDI-TOF mass spectrometry analysis of the native protein revealed a molecular mass at m/z of 63,225.…”
Section: Isoforms Of Ebulinmentioning
confidence: 99%